Determining Components of Dance Interpretation for Encouraging Dance Teacher Interpretation Skills - Vītola, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article explores development possibilities of future dance teachers’ interpretation skills based on the findings on interpretation and its underlying components in the dance by philosophy and theory scientists. Dance is a combination of movement and art - a specific form, a system of codes with certain elements. Dance as a work of art – a cultural product – is characterized exactly by its interpretation eventuality – performer’s artistic activity. Interpretation possibility in dance is determined by knowledge, skills and skills in dance language, as well as the use of this language within a certain dance genre and style in expressing one’s individual style and message. Aim of the Article is to analyze key components of Dance Interpretation and to substantiate their importance for encouraging Dance Teacher Interpretation Skills. The Article use both theoretical research method and scientific knowledge and observations during practical work at Riga Teacher Training and Educational Management Academy (RTTEMA).